2007
DOI: 10.1016/j.vaccine.2006.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant-enhanced antibody responses to recombinant proteins correlates with protection of mice and monkeys to orthopoxvirus challenges

Abstract: Recombinant proteins are being evaluated as smallpox and monkeypox vaccines because of their perceived safety compared to live vaccinia virus. Previously, we demonstrated that three or more injections of a Ribi-type adjuvant with a combination of three proteins from the outer membranes of intracellular (L1 protein) and extracellular (A33 and B5 proteins) forms of vaccinia virus protected mice against a lethal intranasal challenge with vaccinia virus. Here, we compared several adjuvants and found that QS-21 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
54
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 59 publications
6
54
0
Order By: Relevance
“…In previous studies, protection elicited by a protein or DNA vaccine targeting both infectious forms required three or four vaccinations. Recently, it was shown in mice that purified L1 and A33 proteins could elicit a protective antibody response after only two vaccinations if certain adjuvants were used [49]. Here, we demonstrated that delivery of the 4pox antigens, in the absence of adjuvants, could generate protective immune responses after only two vaccinations (Figs.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In previous studies, protection elicited by a protein or DNA vaccine targeting both infectious forms required three or four vaccinations. Recently, it was shown in mice that purified L1 and A33 proteins could elicit a protective antibody response after only two vaccinations if certain adjuvants were used [49]. Here, we demonstrated that delivery of the 4pox antigens, in the absence of adjuvants, could generate protective immune responses after only two vaccinations (Figs.…”
Section: Discussionsupporting
confidence: 52%
“…We, and others, have shown that vaccines comprised of combinations of immunogens targeting both infectious forms of orthopoxvirus, IMV and EEV, provides superior protection versus targeting only IMV or EEV [19][20][21][22][23][24]41,49,50]. IMV neutralizing antibodies, including those against L1 and A27, neutralize virus in the initial exposure and also can eliminate any IMV released from infected cells that are lysed or EEV that are disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike alum, CpG ODN has been shown to be a strongly Th1 biased immunostimulant, showing synergy with alum to promote a mixed Th1 and Th2 pathway. This balancing of antibody responses leads to an increase in total antibody titers [10,[21][22][23][24]. In this study, the comparison of antibody responses between Alhydrogel formulations with and without CPG 7909 was performed with the malarial antigen conjugated to rEPA.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with nonhuman primates or mice have also demonstrated that immunization with baculovirus-expressed recombinant proteins or DNA vaccines composed of different combinations of IMV-and EEVassociated proteins-such as A33R, B5R, and L1R (14,15), A27L, A33R, L1R, and B5R (21), or A27L, B5R, L1R, A33R, and D8L (41)-result in the induction of high levels of neutralizing antibodies and in the protection of mice from lethal challenge with vaccinia virus. In this study, we describe the expression of immunogenic recombinant A27L, D8L, and B5R vaccinia virus proteins by E. coli and demonstrate that subcutaneous immunization of BALB/c mice stimulated high levels of protein-specific and virus-cross-reactive immunoglobulin G (IgG) responses.…”
mentioning
confidence: 99%